Peran manusia sebagai khalifah di muka bumi dari perspektif ekologis dalam ajaran agama Islam - Marpaung, Reza Rahmad (Maliki Interdisciplinary Journal, 2023)
Damage to nature and the environment is often not the result of aging natural processes, but is caused by human actions that are not correct in protecting and utilizing it. Islamic religious teachings contain many verses of the Qur'an and the hadith of the Prophet Muhammad which emphasize the obligation of humans to protect and manage nature. Humans will be held accountable for their actions and may not act arbitrarily in managing the universe. This article will discuss further about the role of humans as caliphs on earth from an ecological perspective in the teachings of Islam. The duty of humans as caliphs is to protect nature and its ecosystem with unity and mutual respect in order to live life according to Islamic religious teachings for survival together.